2012
DOI: 10.1371/journal.pone.0045539
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a Tip60 Specific Inhibitor, NU9056, in Prostate Cancer

Abstract: Tip60 (KAT5) is a histone acetyltransferase (HAT enzyme) involved in multiple cellular processes including transcriptional regulation, DNA damage repair and cell signalling. In prostate cancer, aggressive cases over-express Tip60 which functions as an androgen receptor co-activator via direct acetylation of lysine residues within the KLKK motif of the receptor hinge region. The purpose of this study was to identify and characterise a Tip60 acetylase inhibitor. High-throughput screening revealed an isothiazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
100
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 38 publications
(48 reference statements)
3
100
0
Order By: Relevance
“…Our findings provide new insights into the previously under-appreciated roles of histone hyper-acetylation during cancer development. Recently, small molecule KAT inhibitors have demonstrated relevance in oncology (17,47), thereby providing an additional strategy for combating cancer through the manipulation of histone acetylation. Given the diverse cellular roles of KATs and their working mechanism within transcription factor-containing complexes, KAT inhibitors face the same challenge of a lack of specificity that hampers their therapeutic application in cancer cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings provide new insights into the previously under-appreciated roles of histone hyper-acetylation during cancer development. Recently, small molecule KAT inhibitors have demonstrated relevance in oncology (17,47), thereby providing an additional strategy for combating cancer through the manipulation of histone acetylation. Given the diverse cellular roles of KATs and their working mechanism within transcription factor-containing complexes, KAT inhibitors face the same challenge of a lack of specificity that hampers their therapeutic application in cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive cases of prostate cancers have been found to exhibit overexpression of the KAT Tip60, the extent of which correlates with disease progression (17,18). In contrast, another report has suggested that Tip60 is required for the expression of the tumor metastasis suppressor KAI1 in prostate cancer cell lines, suggesting that Tip60 is a tumor suppressor (19).…”
mentioning
confidence: 99%
“…To measure colony-forming ability cells were reverse transfected with siRNA for 72 h, followed by reseeding at varying cell densities and incubated for 14 days to allow colony formation and stained with crystal violet. Colonies were counted and the surviving fraction calculated (31).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the p300/CBP and GCN5/PCAF classes of HATs were minimally or not involved in the suppression of cPLA 2 α upregulation. In contrast, treatment of cells with theTip60-specific HAT inhibitor NU9056 [77] led to significant reduction of TSA-induced upregulation of cPLA 2 α mRNA expression, suggesting a role of Tip60 in cPLA 2 α expression. We further showed that NU9056 inhibited MS-275-induced upregulation of cPLA 2 α mRNA, indicating that the class I HDACs and Tip60 HAT are specific enzymes involved in epigenetic regulation of cPLA 2 .…”
Section: Discussionmentioning
confidence: 85%
“…We further showed that NU9056 inhibited MS-275-induced upregulation of cPLA 2 α mRNA, indicating that the class I HDACs and Tip60 HAT are specific enzymes involved in epigenetic regulation of cPLA 2 . HDAC inhibitors TSA and MS-275 induce acetylation of H3K9, H3K14, and trimethylation of H3K4 [65,[77][78][79][80] (Table 1). Inhibition of the Tip60 HAT by the synthetic compound, NU9056, has been reported to cause reduction in acetylation levels of H3K14, H4K8, and H4K16 [77] (Table 1).…”
Section: Discussionmentioning
confidence: 99%